EFFECT OF AN 8 WEEKS OF PHYSICAL FITNESS PROGRAM TO IMPROVE THE LEVEL OF PHYSICAL FITNESS ELEMENTS ASSOCIATED WITH HEALTH IN GIRLS ADOLESCENTS - عطا الله, أحمد; دحون, العمري; طاهر, طاهر; مصطفي, طيب (European Journal of Physical Education and Sport Science, 2018)
The aim of this study was to identify the effect of physical fitness program to improve the level of some health - related fitness elements in girls adolescents. Methods: Twenty adolescent girls volunteers (16.42 ± 0.28 years) participated in the study and were divided into two equal groups, 10 were assigned to the intervention group (IG) and 10 in a co ntrol group (CG). The participants in (IG) completed a 30 - 60 minute training session 3 times per week for 8 weeks at moderate intensity for the first 4 weeks and high intensity for the last 4 weeks. Performance on the 20 - meter shuttle run test, Push - up, Cu rl - Up, Sit and Reach flexibility, were assessed at baseline and post - intervention. Results: At post measurement, Health - related fitness was higher (p < 0.05) in (IG) than in (CG) for cardiorespiratory fitness, muscular strength, muscular endurance and fle xibility. Over 8 weeks, the between - group analysis revealed that training program had a large beneficial effect. Conclusion: The results indicate that an eight - week physical fitness program was effective in enhancing cardiorespiratory fitness, muscular str ength, muscular endurance and flexibility among Algerian secondary school girls
Keywords: physical fitness program, physical fitness elements associated with health, girls adolescents